DOZ047.72: Three-dimensional printing for preoperative planning of open laryngotracheal surgery. (24th June 2019) - Fishman, G; Wasserzug, O; Berman, P; Golden, E; DeRow, A
Abstract: Background: Three-dimensional (3D) printing is being employed in a variety of surgical specialties to improve patient care. These models enable preoperative in vitro planning, advanced resident training, and better patient education. 3D models of the tracheobronchial tree that can simulate bronchoscopy and 3D printed cricoid cartilage models for balloon dilation training have been reported. A 3D model for preoperative planning of open laryngotracheal surgery has not been reported. Objectives: The objective of this study was to report preliminary results with the employment of 3D printing technology for preoperative planning of laryngotracheoplasty (LTP) and cricotracheal resection (CTR). Materials and Methods: Actual-size 3D models of the upper airway, from the level of the base of tongue to the level of the carina, have been created by the surgical 3D printing lab in the medical center. The models were based on computed tomography of two patients who were scheduled for LTP and CTR. The models were composed of several elements: the framework of the larynx and the trachea, the air column, the cannula, and the peri-stomal region. Results: Two models were created, a model of a patient with grade III subglottic stenosis who subsequently underwent LTP and a model of a patient with grade IV subglottic stenosis who subsequently underwent CTR and end to end anastomosis. The 3D models were found to be useful for preoperative planning of the incision site in the trachea, the status of the tracheal and laryngeal framework, the length of the diseased segment, and the length of the rib cartilage graft to be harvested. Conclusions: The preliminary results of this study imply that 3D models can be useful for preoperative planning of open laryngotracheal surgery. Further experience is required to establish its efficacy, the optimal model design, and cost effectiveness.